International adaptation of Meaning-Centered Psychotherapy for Latinos: Providers' views on pre-implementation - Costas Muñiz, Rosario (2022)
This qualitative study aims to identify facilitators of and barriers to the implementation of Meaning-Centered Psychotherapy (MCP) by providers of mental health services to Latinos in the US and Latin America using the practical, robust implementation and sustainability model (PRISM). This information will be used to increase usability and acceptability of MCP for Latino patients with cancer and their providers in Latin America and the US.